Ameliorating the positive temperature feedback coefficient for an MSR fueled with transuranic elements. (15th September 2021) - Zou, Chunyan; Yu, Chenggang; Wu, Jianhui; Cai, Xiangzhou; Chen, Jingen
Highlights: Analysis of ameliorating the positive TFC for a TRU-fueled MSR is analyzed. Two effective solutions are proposed to ameliorate the positive TFC. With a hectogram of 167 Er or MA ratio over 50%, the TFC turns to be negative. Abstract: Transuranic (TRU) elements can be used as an alluring fuel in a graphite-moderated Molten Salt Reactor (MSR) with liquid fuel and online reprocessing. However, the positive temperature feedback coefficient (TFC) stemming from the resolvable fission resonances of Pu-239 and Pu-241 at thermal neutron energies should be addressed. The aim of this study is to propose an effective solution to ameliorate the positive TFC, by adding Er-167 into the fuel salt or adjusting the minor actinides (MA) ratio in TRU. Er-167, with a strong capture resonance cross section of about 10, 000 barns at 0.5 eV, is one of the most promising poisons. After adding Er-167 into the fuel salt with hectogram scale, the fuel TFC is decreased significantly to below −10 pcm/K and the total TFC to −2 pcm/K correspondingly. Similar to Er-167, some MA isotopes, especially Np-237 (at 0.5 eV) and Am-241 (at 0.3 eV, 0.6 eV and 1.1 eV) reveal significant capture resonance cross sections (>1000 barns). In this way, increasing the MA ratio in TRU is another available approach to obtain a negative TFC. The simulated results show that adjusting the MA ratio up to 50% can ameliorate the TFC efficiently. Combing the negative TFC and the salt solubility limit, only a narrow region of the fuel volume fraction lower than 25% can meet the two requirements, and the eligible region becomes smaller for a lower MA ratio.